Solusi Startup Kedai Kopi di Indonesia Agar Tetap Bertahan Selama Pandemi COVID-19 - Nandini P. N.; Kevin W.; Michelle C. K.; Marsha A.; Fransisca A. W.; Joshua C. S.; Ruth N. S.; Muhammad Ainur R. (Universitas Ciputra Surabaya, 2020)
As we know that in Indonesia there are many startup businesses that have sprung up, one of which is a coffee shop. This is due to changes in the lifestyle of the Indonesian people who are starting to like drinking coffee. This lifestyle change creates new opportunities to build a coffee shop business. However, with the current condition of Indonesia, which is a coronavirus pandemic or better known as COVID-19, the opportunity to build startups is experiencing obstacles. The government's call for social distancing has caused coffee shops to experience a significant decrease in income. For this reason, coffee shop startups in Indonesia are currently taking various ways to overcome the decline in income they are experiencing. One of them is doing promotion using social media. Promotions are carried out using a different approach than usual. This difference can be seen from those previously using promos such as buy 1 get 1 or discounted prices. However, with this pandemic, various startup businesses are competing to carry out campaigns with an emotional bonding approach. Emotional bonding in question is like using this COVID-19 pandemic to care for each other with others. This research was conducted using qualitative research methods through literature studies and interviews with several coffee shops affected by COVID-19. Keywords: Startup, coffee shops, COVID-19, campaign, promotion